KESIAPAN ANAK MASUK SEKOLAH DASAR DITINJAU DARI POLA ASUH ORANG TUA - Andia Kusuma Damayanti; Essha Paulina (PSIKOVIDYA, 2016)
The purpose of this study was to determine differences in the readiness of children attend primary school in terms of parenting parents based on the theory that Diana Baumrind Authoritarian, Permissive, Authoritative. Theory readiness of children attend primary school used was based on the theory of Prof. F.J. Monks, Drs. H. Rost and Drs. N.H. Coffie (2011). This research is a quantitative study, data were collected using methods Nijmeegse Schoolbekwaamheids Test (NST) for school readiness while data parenting parents were taken by questionnaire. The subjects were children of Restu Ibu Islamic Kindergarten and TKIT Robbani in Malang, amounting to 56 people. Subject taken using purposive random sampling method. The characteristics are as follows: 1) pure disciple is not moving; 2) children kindergarten class B. The research data was analyzed by analysis of variance (ANOVA). The results showed that there was no significant difference in the readiness of children attend primary school in terms of parenting parents.